(untitled) (Superficies y Vacío, 2012)
In this work, hydroxyapatite nanostructured powders were prepared with different crystallinity degree, crystal size and morphology using a simple aqueous precipitation method varying the pH and temperature parameters. We found that at higher pH values the crystal size grows and crystallinity was improved; at higher temperatures there is also a crystal size growth and crystallinity improving but this change is more significant, a change in the morphology of the nanopowders was also observed. Using XRD patterns and Rietveld analysis we found that the crystal size change from 9.15 to 26.4 nm. The prepared powders are highly agglomerated with a pseudo-spherical and rod-like morphology.